Culture coding - a method for diversifying artefact associations in design ideation. Issue 3 (3rd July 2022) - Pejoska, Jana; Durall, Eva; Bauters, Merja; Leinonen, Teemu
ABSTRACT: It can be claimed that technological systems are, in some ways, reflections of the designers' way of thinking. These designs affect the behavior of the users and contribute to the reproduction of future designs, thus strengthening the existing human-technology relations. To address these issues critically, there is a need to challenge design ideation processes for generating a larger variety of design proposals that can contribute to varied users and user behavior. For this purpose, we propose a new method- Culture Coding, that can complement design ideation processes where generating, developing, and elaborating ideas is crucial. In this qualitative study, we explore the value of the proposed method in design by using design activities and a research-through-design approach. The experimental setup consists of two Design Cases where study participants contributed by taking part in two co-design workshops. The findings of the study indicate that Culture Coding may help to guide attention to new perspectives and challenge assumptions of the design context.